2020
DOI: 10.1108/ejim-12-2019-0350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge search on product and process innovation: mediating role of absorptive capacity and moderating role of IT capability

Abstract: PurposeMore enterprises adopt open innovation by breaking technological or organizational boundaries to seek internal and external knowledge when they face a fiercely competitive environment, complex market demands, and increasingly rapid technological change. In this context, a knowledge search strategy is regarded as an effective means of obtaining inside and outside resources and an important way to break the innovation bottleneck. Moreover, information technology (IT) is deemed an important asset for sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
(74 reference statements)
2
23
0
Order By: Relevance
“…From the searching to the innovation process, valuable knowledge is regarded as one of the most significant components for dealing with technological transformation, establishing long-term competitive advantage, and enhancing innovative capabilities via radical and incremental innovation (Ndofor and Levitas, 2004;Shehzad et al, 2021b). Moreover, Knowledge, on the other hand, does not directly transfer into product or process innovation; it requires the facilitation of firm resources and expertise throughout the identification, acquisition, transformation, and exploitation processes (Gao et al, 2020). The researcher asserted that innovation results from human agents employing IT to strengthen or build new organizational resources that assist the firm in developing new goods or services (Chatterjee et al, 2020).…”
Section: Stimulating Firm Innovation Capability 905mentioning
confidence: 99%
See 3 more Smart Citations
“…From the searching to the innovation process, valuable knowledge is regarded as one of the most significant components for dealing with technological transformation, establishing long-term competitive advantage, and enhancing innovative capabilities via radical and incremental innovation (Ndofor and Levitas, 2004;Shehzad et al, 2021b). Moreover, Knowledge, on the other hand, does not directly transfer into product or process innovation; it requires the facilitation of firm resources and expertise throughout the identification, acquisition, transformation, and exploitation processes (Gao et al, 2020). The researcher asserted that innovation results from human agents employing IT to strengthen or build new organizational resources that assist the firm in developing new goods or services (Chatterjee et al, 2020).…”
Section: Stimulating Firm Innovation Capability 905mentioning
confidence: 99%
“…Researchers indicated that knowledge sources (both internal and external) assist organizations in enhancing their innovation capability (Dost et al, 2019;Shehzad et al, 2022). However, enterprises may take full advantage of these learning opportunities only if they have enough fundamental R&D, absorptive, or competence (Gao et al, 2020). With the fast advancement of technology, IT has emerged as a critical effective resource input for organizations' knowledge sources and innovation activities, owing to its efficiency in gathering, processing, and disseminating organizational knowledge (Alavi and Leidner, 2001; Stimulating firm innovation capability Dong and Netten, 2017).…”
Section: Mediating Role It Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…org/index.php/catalog/1559. is dataset has also been used extensively in recent research (e.g., Gao et al [40]; Mu et al [41]; Wang and Qi [42]; Zhu et al [43]), which demonstrates its validity and potential.…”
Section: Sample Selection and Data Collectionmentioning
confidence: 94%